The Influence Of Financial Literacy, Budgeting Planning, And Investment Knowledge On Personal Financial Management Case Study: Kediri City Students - Yunianti, Azzahra Dwi; Zahro, Nur Andini Fatimatuz; Paradita, Bella (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The ability to manage personal finances is important, especially for students who are learning to be financially independent. This study aims to analyze the effect of financial literacy, budget planning, and investment understanding on personal financial management. Data were obtained through structured questionnaires distributed to college students in Kediri City. The analysis technique used multiple linear regression to measure the effect of each variable. The results show that financial literacy, budget planning, and investment understanding have a significant effect, both individually and together, on students' ability to manage finances. Financial literacy makes the greatest contribution compared to other variables. This shows that students with a good understanding of money management and investment tend to be more able to manage their finances effectively. These findings underline the importance of financial education programs that focus on financial literacy, budget management, and investment to increase students' independence in managing personal finances. Educational institutions have a strategic role in supporting this through training and practical learning